2014
DOI: 10.1371/journal.pone.0096668
|View full text |Cite
|
Sign up to set email alerts
|

Measles Case Fatality Rate in Bihar, India, 2011–12

Abstract: BackgroundUpdated estimates of measles case fatality rates (CFR) are critical for monitoring progress towards measles elimination goals. India accounted for 36% of total measles deaths occurred globally in 2011. We conducted a retrospective cohort study to estimate measles CFR and identify the risk factors for measles death in Bihar–one of the north Indian states historically known for its low vaccination coverage.MethodsWe systematically selected 16 of the 31 laboratory-confirmed measles outbreaks occurring i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
11
1
Order By: Relevance
“…The case fatality rate from measles is estimated to be 3-5% in developing countries but may reach more than 10% during epidemics [ 2 ]. The CFR observed in our study was comparable to the findings of measles outbreak investigations conducted in Guji zone of Ethiopia (CFR=0.2%) [ 21 ] and in Bihar, India (CFR=0.78%) [ 24 ]. However, it is lower than the report of outbreak investigations conducted in Simada district of South Gonder zone, Ethiopia (CFR=13.4%) [ 22 ] and in Kebridehar town of Somali region, Ethiopia (1.8%) [ 15 ], Herena and Dawe-Serer districts of Bale Zone of Ethiopia (9.1%) [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…The case fatality rate from measles is estimated to be 3-5% in developing countries but may reach more than 10% during epidemics [ 2 ]. The CFR observed in our study was comparable to the findings of measles outbreak investigations conducted in Guji zone of Ethiopia (CFR=0.2%) [ 21 ] and in Bihar, India (CFR=0.78%) [ 24 ]. However, it is lower than the report of outbreak investigations conducted in Simada district of South Gonder zone, Ethiopia (CFR=13.4%) [ 22 ] and in Kebridehar town of Somali region, Ethiopia (1.8%) [ 15 ], Herena and Dawe-Serer districts of Bale Zone of Ethiopia (9.1%) [ 25 ].…”
Section: Discussionsupporting
confidence: 87%
“…Another systematic review of studies in 12 Indian states published over four decades revealed that the median case fatality ratio was 1.63% ( 8 ). Furthermore, the higher case fatality ratio was reported among under-five children and children from the backward class ( 11 ).…”
mentioning
confidence: 99%
“…Thus, substantial downward revisions of WHO modeled estimates are likely needed. The relationship between measles cases and deaths in India is also uncertain, given that WHO incidence estimates are inconsistent with documented case fatality rates in India which range from 0.8–1.4% (Sudfeld and Halsey, 2009; Verguet et al, 2017; Wolfson et al, 2009; World Health Organization, 2016; World Health Organization, 2018b; Murhekar et al, 2014). Our direct data should help to redefine current estimates of measles mortality and number of infections in India.…”
Section: Discussionmentioning
confidence: 99%